Empowering Housewives through Vertiponic-Chicken Integration Technology to Promote Self-Sufficient Food Production in Urban Home Gardens: A Case Study of BTN Kolhua, Kupang City (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program was motivated by the underutilization of home yards in BTN Kolhua, Kupang City, the lack of public awareness regarding the potential of urban agriculture integration, and the opportunity to enhance food self-sufficiency as a means to stabilize household economies. The objective of this program was to implement a vertiponic-chicken integration model to improve the capacity, knowledge, and skills of housewives in producing food independently and sustainably. Activities were conducted using a participatory-educational approach, which included technical training, mentoring, and evaluation. The results showed an increase in vegetable and egg consumption from backyard production, kitchen cost savings of up to 69%, and a transformation of the role of housewives from food consumers to producers. Active participation and high enthusiasm during the training indicated the success of the applied method. This program proved effective in promoting household food security and has the potential to be replicated in other urban areas.